100 Re-introduction of Pre-hospital Thrombolysis could Improve STEMI Outcomes when Primary Percutaneous Coronary Intervention is Delayed. (3rd June 2016) - Mahendiran, Thabo; McKenzie, Dan; Newton, Judith; Rowe, Rachael; Clarkson, Jacqueline; Dayer, Mark
Abstract : Introduction: Primary percutaneous coronary intervention (PPCI) is the treatment of choice for STEMI in the UK. Before this, thrombolysis represented the main treatment option, delivered in hospital (in-hospital thrombolysis, IHT) or prior to arrival (pre-hospital thrombolysis, PHT). Key to acceptance of the PPCI model is the timeliness of its delivery, with NICE recommending that PPCI should be delivered within 120 min of when fibrinolysis could have been given. Methods: We undertook a retrospective observational study to compare the outcome of patients with STEMI treated with either PPCI or thrombolysis (IHT or PHT) in a medium sized UK district general hospital. Data were obtained from the Myocardial Ischaemia National Audit Project (MINAP) database for patients admitted between 26/02/2002 and 11/11/2013 with a diagnosis of STEMI. Exclusion criteria were: LBBB, pre-hospital cardiac arrest, less than one year of follow up. Patients (n = 1290) were analysed according to the reperfusion modality employed: PHT (n = 124), IHT (n = 354), PPCI (n = 664), no reperfusion therapy (n = 148). There were no significant differences in baseline characteristics of the three intervention groups (Table 1). Results: Median symptom-to-reperfusion time was shortest for PHT (104 min, IQR 73–171), compared with IHT (156 min, IQR 113–253) and PPCI (162 min, IQR 121–275). Median first contact-to-reperfusion time, that is, the time between first physical contact with emergency medical services and reperfusion, was also shortest with PHT (32 min, IQR 24–40) when compared with IHT (59 min, IQR 40–82) and PPCI (82 min, IQR 68–97). Mortality was significantly lower with PPCI compared with IHT at 30 days (4.5% vs 10.5%, P = 0.0005) and 1 year (7.5% vs 14.4%; P = 0.0006). However, PHT was associated with lower mortality when compared with PPCI at 30 days (0% vs 4.5%, P = 0.009) and 1 year (1.6% vs 7.5%; P = 0.01), and with IHT at 30 days (0.0% vs 10.5%; P < 0.0001) and 1 year (1.6% vs 14.4%, P < 0.0001). The sub-group of patients treated with PPCI with a first contact-to-reperfusion time of ≤90 min was shown to have no significant difference in mortality compared with PHT at 30 days (2.3% vs 0.0%, P = 0.13) and 1 year (4.5% vs 1.6%, P = 0.19). However, patients treated with PPCI with a first contact-to-reperfusion time of 91–120 min were shown to have significantly higher mortality when compared with PHT at 30 days (5.8% vs 0.0%, P = 0.004) and 1 year (9.5% vs 1.6%, P = 0.004). PPCI with first contact-to-reperfusion times of >120 min had even higher mortality rates when compared with PHT at 30 days (18.4% vs 0.0%, P < 0.0001) and 1 year (26.5% vs 1.6%, P < 0.0001) (Table 2). Conclusion: This analysis highlights the importance of the timeliness of reperfusion in patient outcomes in PPCI. Furthermore, it suggests that PHT may still represent a viable reperfusion option in the management of STEMI, particularly if significant delays in transfer to a PPCI centre are expected.